The Fruit of the Spirit and Falulu Fohalowo: Synergy of Christian Values and Nias Culture in Character Education for Teenagers - Niat Hati Waruwu; Etika Merlin Gea; Wira Zai (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2025)
This article aims to examine the synergy between the values of the Fruit of the Spirit (Galatians 5:22–23) and the cultural values of Falulu Fohalowo from the people of Nias as a basis in the formation of the character of today's Christian youth. This research uses a literature study method by examining various sources such as the Bible, theological literature, books, and relevant scientific articles. The results of the study show that the Fruit of the Spirit emphasizes inner transformation through the development of love, joy, peace, patience, kindness, loyalty, gentleness, and self-mastery, while Falulu Fohalowo emphasizes social responsibility, mutual cooperation, and respect for others in the context of community. The synergy between the two results in a holistic approach to adolescent character education that integrates spirituality, value understanding, and tangible action. Thus, the contextual application of the values of the Spirit Fruit and Falulu Fohalowo in Christian Religious Education can be an effective strategy in forming adolescents who are faithful, have social character, and are able to live Christian values in the midst of modern cultural challenges.